SPORTS AND SOCIAL ASSISTANCE POLICIES: AN ANALYSIS OF THE PROGRAM PROJOVEM ADOLESCENTE - Felipe Barbosa Passos; Pedro Fernando Avalone Athayde (Journal of Physical Education)
ABSTRACT This work sought to analyze sports in the service offered through Brazilian Social Assistance Policies, the Service for Coexistence and Community Reinforcement (SCCR), with a central axis of analysis in the qualification program for the people aged 15 to 17, called Projovem Adolescente. Here we explain the theoretical and conceptual understanding of SCCR in Brazil and its structuring axes. We also describe the theoretical and methodological proposal for sports in Projovem and develop a methodology for analysis that proposes to reveal whether the sports experience proposed in the program is aligned with the delimitations of the SCCR. This article is characterized by a qualitative social research of exploratory nature, using bibliographical reviews and document research. We concluded that there is considerable alignment between Projovem's sports field proposals and SCCR regulations, in addition to its success in its theoretical conception, from a critical perspective on sports and advances in originality.